Light Microscopic Study of Cervical smear in a Tertiary Hospital at Dhaka - Rahman, MT; Afroz, N; Tahmin, T; Nipa, NN; Faisal, RH; Choudhury, SR (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):208-12. The abstract of this article is available on the PubMed website